Molecular determination of kleptoplast origins from the sea slug Plakobranchus ocellatus (Sacoglossa, Gastropoda) reveals cryptic bryopsidalean (Chlorophyta) diversity in the Hawaiian Islands. Issue 3 (21st February 2017) - Wade, Rachael M.; Sherwood, Alison R.
Abstract : The sacoglossan sea slug species complex Plakobranchus ocellatus is a common algivore throughout the tropical Pacific, including the Hawaiian Islands. Plakobranchus ocellatus is kleptoplastic—it sequesters and retains algal chloroplasts—a characteristic that can be exploited to molecularly characterize diminutive bryopsidalean algae that are typically difficult to locate, collect, and identify. Previous DNA barcode analyses of both P. ocellatus and its kleptoplasts have been conducted primarily in the western Pacific and have only minimally sampled the most eastern populations in the Hawaiian Islands. Using two chloroplast markers, rbc L and tuf A, kleptoplast samples from an Oahu population of P. ocellatus were amplified and cloned to identify their algal sources. Plakobranchus ocellatus sequester chloroplasts from up to 11 bryopsidalean algal species, all but one being diminutive in thallus size. Notably, eight of the detected algal species were new records to the Hawaiian Islands. A sequestration preference study demonstrated that the O'ahu population of P. ocellatus preferentially sequesters chloroplasts from diminutive, epilithic taxa. Using cox I barcoding of P. ocellatus, we showed the O'ahu population to be part of a clade that includes sequences from the neighboring island Maui, Australia, and the Philippines. The use of P. ocellatus as a novel sampling tool allows the exploration of the green algal community diversity and composition at a fine scale.